1986
DOI: 10.1017/s0031182000064155
|View full text |Cite
|
Sign up to set email alerts
|

Echinococcus granulosus infection in mice: host responses during primary and secondary infection

Abstract: The reaction of Balb/c mice to primary and secondary subcutaneous infection with Echinococcus granulosus protoscoleces (PSC) is described. From 3 to 14 days following primary exposure to PSC, draining lymph nodes increase in weight and there is expansion of T and B lymphocyte populations, enhancement of in vitro lymphocyte transformational responses and production of PSC-specific IgM and IgE antibodies. Despite the persistence of viable PSC in host tissues, lymphocyte responses decline to pre-infection values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…Likewise, Younuset al, (2016) have been related these changes to the lytic effect of the newly developing E. granulosus hydatid cysts. These results are in agreement with the findings of Al -Nasiri, 2006;Moraitakiet al, 2010; Khalaf, 2013.Previous studies in experimentally induced secondary infections in mice, intraperitoneally injected PSC are surrounded by a considerable cellular infiltration within 3 days, initially involving activated macrophages and subsequently including neutrophils, eosinophils, and lymphocytes ( Richards et al, 1983;Riley et al, 1986;Riley et al, 1985).As far as, red blood cells, platelets, hemoglobin and packed cell volume are usually kept in normal levels through a balance between the new formation and the destruction of old cells in the control group. Our investigation recorded a significant decrease in these parameters which come in a dose and time-dependent mannerthat may be attributed to increased hemolysis or disturbance inthehemopoietin system whichslow of its production (Guyton, 1993 Our biochemical results revealed a marked increase in glucose in the experimentally infected animals that may be due to the effect of the infection on the liver which play an important role in the glucose metabolism (Khalaf, 2013) or occurrence of glycolysis and gluconeogenesis cycles which related to energy production within parasite cyst(ElBayatietal., 2010).…”
Section: Discussion:-supporting
confidence: 91%
“…Likewise, Younuset al, (2016) have been related these changes to the lytic effect of the newly developing E. granulosus hydatid cysts. These results are in agreement with the findings of Al -Nasiri, 2006;Moraitakiet al, 2010; Khalaf, 2013.Previous studies in experimentally induced secondary infections in mice, intraperitoneally injected PSC are surrounded by a considerable cellular infiltration within 3 days, initially involving activated macrophages and subsequently including neutrophils, eosinophils, and lymphocytes ( Richards et al, 1983;Riley et al, 1986;Riley et al, 1985).As far as, red blood cells, platelets, hemoglobin and packed cell volume are usually kept in normal levels through a balance between the new formation and the destruction of old cells in the control group. Our investigation recorded a significant decrease in these parameters which come in a dose and time-dependent mannerthat may be attributed to increased hemolysis or disturbance inthehemopoietin system whichslow of its production (Guyton, 1993 Our biochemical results revealed a marked increase in glucose in the experimentally infected animals that may be due to the effect of the infection on the liver which play an important role in the glucose metabolism (Khalaf, 2013) or occurrence of glycolysis and gluconeogenesis cycles which related to energy production within parasite cyst(ElBayatietal., 2010).…”
Section: Discussion:-supporting
confidence: 91%
“…These data suggest that induction of Th2 antibody-mediated immunity with a parallel expansion of Th1-mediated inflammatory responses is an important mechanism of host defense against the metacestode (111). Local inflammatory reactions to PSC at the site of injection are intense, involving neutrophils, eosinophils, macrophages, and mast cells (221).…”
Section: Established Cystsmentioning
confidence: 90%
“…In experimentally induced secondary infections in mice, intraperitoneally injected PSC are surrounded by a considerable cellular infiltration within 3 days, initially involving activated macrophages and subsequently including neutrophils, eosinophils, and lymphocytes (208,221,222). Interleukin-10 (IL-10), IL-4, and IL-5 secreted in vitro by splenocytes can be detected as early as week 1 postinfection (55).…”
Section: Innate Resistance and Early Immunitymentioning
confidence: 99%
“…Numerous studies have demonstrated that humoral immunity plays a crucial role in the protection against E. granulosus (Barriga andAl Khalidi 1986, Haralabidis et al 1995). In experimentally induced secondary infections in mice, intraperitoneally injected PSC are surrounded by considerable cellular infiltration within 3 days, initially by involving activated macrophages and subsequently including neutrophils, eosinophils, and lymphocytes (Richards et al 1983;Riley et al 1985Riley et al , 1986. Only small amount of IgM, IgG1, IgG2a, and IgG3 could be detected early in serum, and higher levels were detectable later (Pater et al 1998).…”
Section: Discussionmentioning
confidence: 99%